The Measure of Processes of Care 20-Item (MPOC-20): Validity and Reliability of the Malay Version - Nor Farah Mohamad Fauzi,; Amy Chen, Ern Ming; Hanif Farhan Mohd Rasdi,; Nur Zakiah Mohd Saat, (Penerbit UKM, 2015)
The paediatric rehabilitation service in Malaysia is shifting from the traditional child-focused approach to a family-centred approach. At present, there is a lack of an evaluation tool to assess to the quality of paediatric rehabilitation services, and whether the services are in line with the principles of the family-centred service. This study was undertaken to assess validity and reliability of the Malay version of the Measure of Processes of Care 20-item (MPOC-20) questionnaire in evaluating family-centered approach in children rehabilitation services in Kuala Lumpur. The original English version of the MPOC-20 was translated into Malay language, before it was administered to 102 parents of children receiving rehabilitation service at the Occupational Therapy Unit, UKM Medical Centre. The component structure of the MPOC-20 Malay version was examined using principal component analysis with Varimax rotation to explore the factor structures after translation. Cronbach’s alpha was calculated to determine the internal consistency reliability of the factors identified in the MPOC-20 Malay version. The resultant four-factor model explained 64 % of the variance in the Malay MPOC-20 responses. All four factors were similar to the five factors described in the original MPOC-20. All the 20 items were retained, with relocation of some items into a new factor. The Malay version of the MPOC-20 showed good internal consistency with Cronbach’s alpha values ranging from 0.75 to 0.90. This study demonstrates that the Malay version of the MPOC-20 is valid and reliable, and is suitable for evaluation of the quality of child rehabilitation services in the Malaysian context.